Stormwater Drainage Design (Case Study: UTHM Campus) - Ibrahim, Rabiatul Najwa; Ahmad, Noor Aliza (Recent Trends in Civil Engineering and Built Environment, 2023)
The impervious surface has risen as a result of development is growing rapidly. All roads, walkways, and parking areas that have significant paved surfaces that are covered by substances such as asphalt, concrete, brick, and stone are referred as impervious area. Impervious surfaces are considered to have poor water permeability as the surface prevents water from penetrating it which can lead to increased surface runoff. Therefore, the objective of this case study is to determine runoff problem at impervious area that may cause flash flood as well as to propose a good design for storm water drainage. In this study, the rational method and Manning’s equation were applied. Rational method was used to determine the peak runoff in the study area and manning’s equation was used to ensure that the stormwater drain designed were able to accommodate peak surface runoff. As a result, it was discovered that the poor infiltration rate in the study area was also a contributing factor to increasing impervious surface runoff. In order to decreased surface runoff on impervious surfaces while minimising the risk of flash floods, the designed stormwater drain should be able to accommodate peak flow. By doing this study, runoff problems were identified and a stormwater drain was developed to mitigate the problem in the study area.